Approach to Non‐Neutropenic Fever in Pediatric Oncology Patients—A Single Institution Study. Issue 12 (14th July 2015) - Ali, Bilal Abou; Hirmas, Nader; Tamim, Hani; Merabi, Zeina; Hanna‐Wakim, Rima; Muwakkit, Samar; Abboud, Miguel; Solh, Hassan El; Saab, Raya
<x xml:space="preserve">Abstract</x> Background Pediatric oncology patients with fever, even when not neutropenic, are known to be at an increased risk of bloodstream infections. However, there are no standard guidelines for management of fever in non‐neutropenic patients, resulting in variability in practice across institutions. Procedure We retrospectively analyzed the clinical characteristics, management, and outcome of all febrile non‐neutropenic episodes in pediatric oncology patients at a single institution over the two‐year period 2011–2012, to identify predictors of bloodstream infections. We assessed the efficacy of a uniform approach to outpatient management of a defined subset of patients at low risk of invasive infections. Results A total of 254 episodes in 83 patients were identified. All patients had implanted central venous catheters (port). Sixty‐two episodes (24%) were triaged as high‐risk and admitted for inpatient management; five (8%) had positive blood cultures. The remaining 192 episodes were triaged as low risk and managed with once daily outpatient intravenous ceftriaxone; three (1.6%) were associated with bacteremia, and 10% required eventual inpatient management. Of all the factors analyzed, only signs of sepsis (lethargy, chills, hypotension) were associated with positive bloodstream infection. Conclusions Treatment of a defined subset of patients with outpatient intravenous ceftriaxone was safe and effective. Signs of sepsis were the only factor significantly associated with bloodstream infection. This study provides a baseline for future prospective studies assessing the safety of withholding antibiotics in this subset of patients. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.